Aspects of the occurrence of depression and suicide risk in health professionals: integrative review (Research, Society and Development, 2022)
The occurrences of depression and suicide are caused by a variety of factors, most of which are motivated by the desire to escape from a life of great psychological suffering. Thus, the present study aims to analyze the scientific production on depression and suicide in health professionals, and to know the aggravating factors for its development during health care practice, from a literature search for studies published between the years 2016 and 2022. The searches were made in the electronic journals Scopus, PubMed, Cinahl and Medline. Using the guiding question: What are the repercussions and main causes of depression and suicide in healthcare professionals? As results, associations were observed between depression and suicidal ideation and work hours, job satisfaction and appreciation, sleep disturbances, bullying, sexism and discrimination; blame culture, shame and fear of reporting; lack of support; stigma and a perceived need to appear invulnerable; work/family conflict, social isolation and alcohol abuse. Therefore, the impacts common to these psychopathologies can induce adverse health care-related events, potentially resulting in patient deaths. It is concluded that the use of harm reduction and prevention strategies, such as the early introduction of psychological and psychiatric therapies, as well as a greater awareness of the population on the subject, predisposes to a decrease in the prevalence rates of depression and suicide.